Daytime Sleepiness in Adults With ADHD: A Pilot Trial With a Multiple Sleep Latency Test. (December 2016) - Sobanski, Esther; Alm, Barbara; Hennig, Oliver; Riemann, Dieter; Feige, Bernd; Schredl, Michael
Objective: To evaluate sleep latency (SL) during the multiple sleep latency test (MSLT) and subjective daytime sleepiness in adult ADHD and controls.Method: Subjective daytime sleepiness was assessed by Epworth Sleepiness Scale (ESS) in 27 unmedicated adults with ADHD and in 182 controls. Thirteen ADHD patients and 26 controls underwent MSLT after one night of polysomnography (PSG).Results: Mean MSLT-SL was 10.6 ± 4.8 min in ADHD and 12.2 ± 4.2 min in controls (n.s.). Mean ESS score was 9.3 ± 4.9 points in ADHD and 6.9 ± 3.4 points in controls ( p < .005). MSLT-SL and ESS scores correlated inversely by trend ( r = −.45, p < .1) but not with ADHD symptoms or ADHD subtype.Conclusion: Adults with ADHD do not differ from controls in mean MSLT-SL but experience increased subjective daytime sleepiness. Patients with subjective higher daytime tiredness fell asleep faster during MSLT.